A blockchain-based IIoT traceability system: ERC-721 tokens for Industry 4.0 - Koustas, Spyridon Georg; Jalowski, Max; Reichenstein, Tobias; Oks, Sascha Julian (Procedia CIRP, 2023)

A cross-domain comparison of application areas for service systems based on cyber-physical systems - Oks, Sascha Julian (8th Service Operations Management Forum, 2015)
Information technology has had a distinct influence on societies, their organizations and industries as well as the lives of their members. The automation of production processes and the usage of personal computers and mobile devices in both work and private related contexts are just a few examples. Nowadays, a further advancement brings inestimable potential based on IT infrastructure: The internet of things. Based on sensors, actuators and data analyzing solutions, cyber-physical systems build the infrastructure for new service systems and business models. Especially for service systems, cyber-physical systems offer a wide range of application fields: First there are end user oriented services systems which can benefit from the functionality and capabilities of cyber-physical systems. Well known examples are services in the field of “smart home” and “smart mobility”. Second, the opportunities for public systems are to mention. Due to the implementation of cyber-physical systems public systems can reach a further level of service quality. Furthermore the interconnection, based on cyber-physical architectures, of these systems allows the emergence of “systems of systems” like “smart grids”. Third, industrial in-plant service systems can profit from the utilization of cyber-physical systems: Besides the widely mentioned profits for inter-machinery communication, the “smart factory” also benefits by integrating the personnel more efficient into production processes. The conducted research compares the three before mentioned application areas in regards of “how cyber-physical systems foster the engineering as well as performance of service systems” for the described users. The methodology of a systematic literature review led to an overview of both chances but also challenges which need to be addressed to enable these individual, economic and organizational potential
Keywords: service systems; service systems engineering; cyber-physical systems

An Application Map for Industrial Cyber-Physical Systems - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin (Industrial Internet of Things – Cybermanufacturing Systems, 2017)
The potential transformation cyber-physical systems can bring to a broad variety of domains is widely discussed in academia and industry. Despite the expected benefits in the industrial domain of further automatization of production processes and the possibility to produce “batch size one” at large-scale production costs, the majority of organizations hesitate in the implementation of cyber-physical systems. This can be attributed to uncertainty decision makers feel, about how to choose right applications of cyber-physical systems and if chosen how to implement these applications to the unique and specific needs of their organization. To address this problem this chapter introduces an application map which includes the spheres smart factory, industrial smart data, industrial smart services, smart products, product-related smart data and product-related smart services. Based on this model, the decision makers are provided a scheme of application fields for utilizing cyber-physical architectures adjusted to their unique business situatio

Bildung als Schlüssel zur Digitalen Transformation und der Mehrwert militärischer Ausbildungsformate - Fritzsche, Albrecht; Oks, Sascha Julian; Mosig, Tim ((Aus)Bildungskongress der Bundeswehr, 2018)

Cyber-physical modeling and simulation: A reference architecture for designing demonstrators for industrial cyber-physical systems - Oks, Sascha Julian; Jalowski, Max; Fritzsche, Albrecht; Möslein, Kathrin (Procedia CIRP, 2019)
The application of models and simulations is well-established in systems engineering and development. To adapt this approach to the digital age, we propose the concept of “cyber-physical modeling and simulation (CPMS)” which enables to constitute cyber-physical systems (CPS) with scalable complexity, modularity and variability in size. Based thereon, we derive a reference architecture for designing demonstrators for industrial CPS. The reference architecture offers a structured design space and attributed components which constitute the demonstrators with regard to their application objectives and scenarios. As a viability assessment, we apply the proposed reference architecture by developing the instantiation “Portable Industrial Demonstrator for Cyber-Physical Systems (PID4CPS)
Keywords: Cyber-physical systems; cyber-physical modeling; simulation; reference architecture; demonstrator

Cyber-physical systems – Can technology be smart? - Oks, Sascha Julian (Forum on Philosophy, Engineering & Technology (fPET), 2016)
Information technology has had a distinct influence on societies, their organizations and industries as well as the lives of their members. The automation of production processes and the usage of personal computers and mobile devices in both work and private related contexts are just a few examples. Nowadays, a further advancement brings inestimable potential based on IT infrastructure: The internet of things. Based on sensors, actuators and data analyzing solutions, cyber-physical systems build the infrastructure for new epoch of technology in use. The term “smart” is often mentioned when cyber-physical systems are discussed in academia and practical oriented communities. But this smart does not refer to the systems users but to the technology itself. Smartness and the underlying intelligence were before characteristics which are strongly connected to living beings with gradations of different species. Even though the term artificial intelligence has been known for more than half a decade and associated developments reached impressive levels like IBM’s Watson until now, human intelligence is still obviously superior when it comes contextual understanding, continuous learning and decision making under unanticipated changing conditions. But how will the world look like if the visions based on cyber-physical systems around the term smart become reality? What if the cyber-physical systems reach a level of smartness that might not match the mental capabilities of humans but which is adequate to replace humans extensively in executing tasks, dangerous activities and basic fields of value creation? The areas of application of smart technologies are quite broad: “Smart home”, “smart health”, “smart mobility”, “smart logistics”, “smart grid”, “smart factory” and further more. When analyzing these ongoing occurrences the following points stand out: The intended application fields for smart technologies fall into a multitude of areas of society and its people. From personal everyday activities and way of live (e.g. smart home) over organizational applications (e.g. smart factory) to infrastructural, economical and governmental scopes (e.g. smart mobility and smart grid). The extensive implementation of cyber-physicals systems and other internet of things applications might exceed former introductions of technology with regard to sociological, industrial and economic impact and change. E.g. in the case of the smart factory the implementation of cyber-physical systems ascribed to the fourth industrial revolution. Artificial intelligence is no longer predominantly just used for analytics and evaluation of data but leaves the cyber space to interact in form of robotic solutions with the physical world. The conducted research reflects the above described development from a philosophical and ethical perspective. By doing so, the following fields and questions find an emphasized consideration: Which consequences does it have, when smart technologies take over a multitude of executing tasks which were formerly conducted by persons and the proportion of executive to creative work changes significantly? Contemporary schools of thought of work ethics are applied to the formulated question. Furthermore a potential disentanglement of personal work and value creation and remuneration finds a philosophical evaluation: Is it desirable to free mankind from the performance of executive activities to offer the opportunity to fully focus on creative and scientific activities? Or is the conduction of executive work a meaningful activity beyond the income-generation? E.g. is it aspirational to approach the undersupply of workforce in elderly care by implementing smart technologies which could execute certain task but would lower the social interaction of care receiving persons? As a result a comparison of different argumentations regarding artificial intelligence, cyber-physical systems and their effect on humans and societies is give
Keywords: cyber-physical systems; technology; human machine interaction

Cyber-Physical Systems in the Context of Industry 4.0: A Review, Categorization and Outlook - Oks, Sascha Julian; Jalowski, Max; Lechner, Michael; Mirschberger, Stefan; Merklein, Marion; Vogel-Heuser, Birgit; Möslein, Kathrin (Information Systems Frontiers, 2022)
Cyber-physical systems (CPS) offer great potential for the digital transformation of industrial value creation in the context of Industry 4.0. They unify and integrate several technological approaches, including big data analysis and artificial intelligence, enhancing real-time monitoring and control of manufacturing processes. An extensive knowledge base formed by various disciplines, including information systems, engineering, and computer science, already exists for CPS. However, this knowledge has not been holistically captured and structured to date. To address this research gap, this study conducts a large-scale literature review of 2365 papers representing the current state of the research and then develops a novel categorization on industrial CPS with 10 sections, 32 areas, and 246 fields. The categorization is presented in hierarchical graphical form and can also be utilized as a web tool. To conclude, a perspective on future research needs and potentials to enhance Industry 4.0 in both research and practice are offere
Keywords: Cyber-physical systems; Industry 4.0; State of research; Categorization

Demonstrating industrial smart product-service systems: Industry 4.0 maturity through stakeholder-oriented development and testing - Koustas, Spyridon Georg; Reichenstein, Tobias; Oks, Sascha Julian; Fuchs, Jonathan; Möslein, Kathrin (Procedia CIRP, 2023)

Demonstratoren im Industrie 4.0-Kontext - Dörr, Luca; Oks, Sascha Julian; Trezl, Jonas; Reichenstein, Tobias; Koustas, Spyridon Georg; Lehmann, Claudia (wt Werkstattstechnik - Online, 2024)
Industrie 4.0 bringt neben vielen Potenzialen auch eine erhebliche Komplexitätssteigerung mit sich. Um dieser effektiv zu begegnen, bieten Demonstratoren einen wertstiftenden Beitrag. Ihr Einsatz ermöglicht eine nutzerzentrierte Systementwicklung mit einhergehender Komplexitätsreduktion durch Modellierung und Simulation. Dieser Beitrag untersucht ihre Potenziale am Beispiel des Projektes „ConSensE“ mit Fokus auf Sensortechnologien und deren Nachrüstun
Keywords: Mensch und Technik; Produktionsarbeit; Sensoren

Design and Evaluation of a Portable Industrial Demonstrator for Cyber-Physical Systems - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin (Proceedings of the 13th International Conference on Design Science Research in Information Systems and Technology, 2018)
The digitization of the industry offers far-reaching potentials in the context of industrial value creation. With the introduction of technologies such as cyber-physical systems (CPS), organizations aim to realize them. However, due to an increase in complexity with regard to system architectures and the number of involved stakeholders, organizations face novel challenges in the process of system development. This research addresses this issue with the de-sign of a portable industrial demonstrator for CPS and a complementary work-shop setting to model and simulate industrial CPS configurations with reduced complexity. Thereby, the solution functions as a boundary object joining differ-ent stakeholder groups to mediate and elaborate a common understanding, moderate conflicting expectations, evaluate and align system configurations and foster stakeholder driven innovations within the system design process. In doing so, the solution offers a new approach for participatory CPS design. The de-signed artifacts are evaluated in the course of interview and observational stud-ies in combination with focus groups. The results reveal that the development of industrial CPS benefits from the use of demonstrators, especially with regard to stakeholder integration.<br
Keywords: Design Science Research; Industrial Demonstrator; Cyber-Physical Systems

Design principles for establishing a multi-sided open innovation platform: lessons learned from an action research study in the medical technology industry - Daiberl, Christofer; Oks, Sascha Julian; Roth, Angela; Möslein, Kathrin; Alter, Steven (Electronic Markets, 2019)
Innovation in the medical technology (med tech) industry has a major impact on well-being in society. Open innovation has the potential to accelerate the development of new or improved healthcare solutions. Building on work system theory (WST), this paper explores how a multi-sided open innovation platform can systematically be established in a German med tech industry cluster in situations where firms had no prior experience with this approach. We aim to uncover problems that may arise and identify opportunities for overcoming them. We performed an action research study in which we implemented and evaluated a multi-sided web-based open innovation platform in four real-world innovation challenges. Analyzing the four different challenges fostered a deeper understanding of the conceptual and organizational aspects of establishing the multi-sided open innovation platform as part of a larger work system. Reflecting on the findings, we developed five design principles that shall support the establishment of multi-sided open innovation platforms in other contexts. Thus, this paper contributes to both theory and practic
Keywords: Multi-sided platforms; Open innovation; Work system theory; Medical technology industry cluster; Action research

Die Rolle von Industrie 4.0-Demonstratoren in der digitalen Transformation – Eine Standpunktbestimmung am Portable Industrial Demonstrator for Cyber-Physical Systems (PID4CPS) - Oks, Sascha Julian; Jalowski, Max; Zansinger, Nina; Möslein, Kathrin (Lernfabriken an beruflichen Schulen – Gewerblich-technische und kaufmännische Perspektiven, 2021)
Die digitale Transformation verändert industrielle Wertschöpfung umfassend und nachhaltig. Dieser disruptive Prozess hat u. a. große Auswirkungen auf die Arbeitsformen, Rollen und Qualifikationsanforderungen in der Produktion sowie in vor- und nachgelagerten Wertschöpfungsstufen. Neben Handlungs-, Fach- und Methodenkompetenzen in der Industriearbeit kommt der generellen Themenkompetenz bezüglich Industrie 4.0 eine immanent wichtige Rolle zu, wenn es darum geht, die Partizipation und Mitbestimmung jeder einzelnen Person an der digitalen Transformation industrieller Wertschöpfung sicherzustellen. Ebenso gilt es, integrative und Stakeholder-zentrierte Systementwicklungsverfahren zu etablieren, um die Einstellungen und Erwartungshaltungen verschiedener Stakeholder-Gruppen zu erfassen und moderieren sowie Konflikte zu regulieren und so letztendlich eine hohe Akzeptanz und Annahme digitaler Technologien und Prozesse sicherzustellen. Dieser Beitrag analysiert und erörtert die Eignung und Einsatzmöglichkeiten von Industrie 4.0-Demonstratoren zu diesen Zwecken. Im Zentrum der Betrachtung steht dabei der Portable Industrial Demonstrator for Cyber-Physical Systems (PID4CPS), der eine etablierte Instanziierung dieser Demonstratorenart darstellt. Besonderes Augenmerk wird auf die Verwendbarkeit von Industrie 4.0-Demonstratoren für die Lehr-/Lern- sowie Aus- und Weiterbildungszwecke in den unterschiedlichen Stufen des Bildungswesens gelegt. Darüber hinaus erfolgt eine vergleichende Gegenüberstellung der Konzepte von Industrie 4.0-Demonstratoren und Lernfabriken, aus der konkreten Handlungs-implikationen zum Einsatz dieser in Lehre sowie Aus- und Weiterbildung abgeleitet werden.<br
Keywords: Industrie 4.0; Demonstrator; Lernfabrik; Simulation; Ausbildung

Die vernetzte Instandhaltung im Kontext von Industrie 4.0 – Perspektiven für die Arbeit der Zukunft - Oks, Sascha Julian (Praxiswissenschaftsdialog Arbeiten 4.0: Vernetzte Prozesse und Assistenzsysteme in der Praxis, 2017)
Keywords: Industrie 4.0; Digitale Transformation; Arbeit 4.0

Embedded vision device integration via OPC UA: Design and evaluation of a neural network-based monitoring system for Industry 4.0 - Oks, Sascha Julian; Zöllner, Sebastian; Jalowski, Max; Fuchs, Jonathan; Möslein, Kathrin (Procedia CIRP, 2021)
Sensor application is a basis for digitized industrial value creation. However, for existing production and logistics systems, sensor retrofitting is accompanied by challenges, including plant heterogeneity and lack of standards. This work addresses this issue through the design, implementation and evaluation of an embedded vision high-bay shelf monitoring system of an Industry 4.0 demonstrator. Utilizing design science research methodologies, the artifact unites the concepts of computer vision, convolutional neural networks and OPC UA for widely applicable and cost-efficient retrofitting. Design principles derived from the artifact’s design and evaluation cycles can serve as abstracted guidelines for designing retrofit visual sensor system
Keywords: Embedded vision; Retrofitted sensor systems; Neural networks; OPC UA; Industry 4.0

Engineering industrial cyber-physical systems: An application map based method - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin (Procedia CIRP, 2018)
The extensive digitization in industry and the advancing introduction of cyber-physical systems (CPS) in manufacturing offer a wide-ranging potential for industrial value creation. To ensure effective engineering processes of these systems, technological and organizational challenges need to be addressed systematically. Thereto, we develop a method for the systematic engineering of industrial CPS in this paper. The operational framework of the suggested method provides a guided process for (1) the selection of application fields for industrial CPS under the consideration of economic and technological necessities as well as (2) guidelines for the subsequent system configuration with components and functionalitie
Keywords: Industrial cyber-physical systems; system configuration; system engineering; method development

Fostering knowledge sharing: Design principles for persuasive digital technologies in open innovation projects - Jalowski, Max; Oks, Sascha Julian; Möslein, Kathrin (Creativity and Innovation Management, 2023)
Integrating knowledge is crucial for open innovation, and digital technologies can play a central role because they support knowledge sharing. In open innovation projects, in particular, little is known about the role of technology. Here, the individual behaviour of users is taken into account concerning the extent to which knowledge is shared. Therefore, persuasive technologies offer the potential to foster sharing. In particular, to facilitate the construction of future digital technologies, this study applies a design science research approach to create and analyse artefacts as a research contribution and develop design principles as a step towards a nascent design theory. We present insights from the design and application of three artefacts in different stages of open innovation processes. Results show that digital technologies can be used for various purposes: to build a common understanding, support design phases, communicate ideas and simplify the application of the technology for the user. Our research provides insights into the role of digital technologies for knowledge sharing in open innovation projects, and four design principles are found to facilitate the construction of future persuasive digital technologies for open innovation project
Keywords: design principles; design science research; digital technologies; knowledge sharing; open innovation; persuasive technology

Führen im Industrie 4.0-Zeitalter: innovativ, balanciert und wertschätzend - Möslein, Kathrin; Oks, Sascha Julian; Wendelken, Anke (præview, 2015)

Importance of user role concepts for the implementation and operation of service systems based on cyber-physical architectures - Oks, Sascha Julian; Fritzsche, Albrecht (innteract, 2015)
Information technology has had a distinct influence on societies, their organizations and industries as well as the lives of their members. Nowadays, a further advancement brings inestimable potential based on IT infrastructure: The internet of things. Based on sensors, actuators and data analyzing solutions, cyber-physical systems build the infrastructure for new processes as well as service systems. In the field of manufacturing the main focus is set on the continuous advancement of automation and fostering further efficiency in the machine based production processes. In addition to this it must be emphasized, how relevant convenient user integration is: Technological progress only reveals its ultimate potential if the users which interact with the system are integrated according to their need
Keywords: user; role concept; service systems; cyber-physical systems; internet of things

Increasing Efficiency in Maintenance Processes Through Modular Service Bundles - Fuchs, Jonathan; Herrmann, Hanna; Oks, Sascha Julian; Sjarov, Martin; Franke, Jörg (Production at the leading edge of technology, Proceedings of the 10th Congress of the German Academic Association for Production Technology (WGP), Dresden, 23-24 September 2020, 2021)
Increasing complexity in production and factory automation represents a significant challenge in context of maintenance. One approach to address complexity is the implementation of automated industrial service bundles, which resemble complex business processes. To enable efficient usage of service bundles, their individual components are designed as functional modules in the form of independent micro services and are compatible with the paradigm of service-oriented architectures. For ubiquitous communication and data exchange between service entities, message-oriented middleware provides an adequate solution. This paper presents an approach for increasing efficiency in maintenance using a service bundle. The use case demonstrates the automated creation of service tickets enriched with necessary information from various source
Keywords: Smart services; Service bundle; Smart maintenance; Process automation

Industrial Cyber-Physical Systems – Advancing Industry 4.0 from Vision to Application - Oks, Sascha Julian (Springer Gabler, 2024)
Cyber-physical systems (CPS) are one of the key concepts of Industry 4.0. Despite their great potentials for industrial value creation, there are challenges, such as a significant increase in complexity, as a result of which the development status of Industry 4.0 is behind expectations. This book addresses this issue with the following research design: In addition to providing a comprehensive foundation of industrial CPS and Industry 4.0, four studies are conducted, each consisting of an exploratory research part and a design science research (DSR) part. In doing so, four perspectives are directed at the topic of industrial CPS: A systemic, a stakeholder-centered, an organizational and a holistic. In conclusion, the contributions are integrated in a summary and the artifacts are incorporated into an overarching methodological framework. Thus, theoretical contributions are derived and concrete practical recommendations for the main target groups of organizations, educational institutions and international delegations provide
Keywords: Design science research; Stakeholder management; Cyber-physical systems; Industry 4.0; Industrial cyber-physical systems; Digitalization; Demonstrator; PID4CPS

Industrial cyber-physical systems from a stakeholder perspective - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin (Proceedings of the R&D Management Conference (RADMA), 2018)
The increasingly progressive digitization of industrial value creation in the context of the fourth industrial revolution is leading to profound change for companies. In this context, technological innovations like industrial cyber-physical systems (CPS) have an impact not only on production processes and service provision but also on the roles and activities of the most diverse actors in the internal and external environment of companies. For the sustainable and successful application of these technologies, it is therefore important to ascertain and analyze the expectations from and attitudes towards industrial CPS of the individual stakeholder groups in order to use this knowledge for the design, implementation and operation of industrial CPS configurations. Utilizing technology acceptance, innovation diffusion and stakeholder theories as a foundation, stakeholder groups are identified and subsequently surveyed via interviews and focus groups within a multiple case study. The subsequent evaluation of the data is based on a qualitative content analysis. The application of an industrial CPS for maintenance in companies within the automotive, supplier and power generation industries sets the empirical field. The results of the study offer a comprehensive overview of stakeholder expectations from and attitudes towards industrial CPS and show existing consensus but also the prevailing discrepancies.<br

Industrie 4.0 erfolgreich implementieren – Eine Morphologie für unternehmensindividuelle Lösungen - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin (4. Markt&Technik Summit Industrie 4.0 & Industrial Internet, 2016)
Unter dem Leitbegriff Industrie 4.0 wird sowohl seitens der Praxis als auch der Wissenschaft diskutiert, inwieweit sich die technologischen Innovationen, die das Internet der Dinge ausmachen, nutzenmaximierend für die Industrie einsetzen lassen. Gerade für die deutsche Industrie mit ihrer führenden Stellung im Bereich der Fabrikausrüster ist es hierbei essentiell, das volle Wertschöpfungspotenzial der Industrie 4.0 zu erschließen. Hierzu gilt es neue Geschäftsmodelle zu entwickeln und erfolgreich am Markt zu etablieren. Dieser Beitrag bietet hierzu den systematischen Ansatz einer Morphologie, die sowohl ein einheitliches Begriffsverständnis ermöglicht als auch konkrete Implementierungsmöglichkeiten für Industrie 4.0-Applikationen bereitstell

Industrie 4.0: Geschäftsmodelle und Umsetzung für den Mittelstand - Barbian, Matthias; Künneth, Ronald; Möslein, Kathrin; Oks, Sascha Julian (2. Markt&Technik Summit Industrie 4.0, 2014)

Industrie 4.0 – von der Vision zur Anwendung: Eine Stakeholder-zentrierte und personalfokussierte Methode - Oks, Sascha Julian; Jalowski, Max (#NUEdialog, 2021)

Innovation KI-basierter Dienstleistungen für die industrielle Wertschöpfung – Ein artefaktzentrierter Ansatz - Jalowski, Max; Roth, Angela; Oks, Sascha Julian; Wilga, Matthäus (Künstliche Intelligenz im Dienstleistungsmanagement, 2021)
Dieser Beitrag zeigt auf, wie insbesondere für kleine und mittlere Unternehmen die Gestaltung und Innovation von KI-basierten Dienstleistungen in der industriellen Wertschöpfung unterstützt werden kann. Dazu werden Herausforderungen bei der Entwicklung KI-basierter Dienstleistungen erhoben und anschließend Artefakte präsentiert, die zur Innovation von Dienstleistungen zum Einsatz kommen. Diese werden basierend auf den zuvor identifizierten Herausforderungen adaptiert, um die Innovation von KI-basierten Dienstleistungen zu ermöglichen.<br

Integrierte Entwicklung smarter Produkt-Service-Systeme - Oks, Sascha Julian; Schymanietz, Martin; Jalowski, Max; Posselt, Tim; Roth, Angela (Smart Services, 2022)
Die Innovation von smarten Produkt-Service-Systemen (sPSS) bietet Unternehmen zahlreiche Potentiale, geht jedoch auch mit nicht zu vernachlässigenden Herausforderungen einher. Diese Studie erhebt den Status quo der Innovation von sPSS, sowohl mittels einer Umfrage unter Unternehmen als auch literaturbasiert, um anschließend acht Gestaltungsleitsätze für integrierte sPSS-Innovationsprozesse abzuleiten. Diese Gestaltungsleitsätze dienen als Grundlage der Gestaltung einer sPSS-Anwendungskarte, die Unternehmen bei der Bewältigung von Herausforderungen und dem Ausschöpfen der Potentiale von sPSS-Innovationen unterstütz

Künstliche Intelligenz als Treiber für Dienstleistungsinnovation - Roth, Angela; Oks, Sascha Julian (Automatisierung und Personalisierung von Dienstleistungen, 2020)
Künstliche Intelligenz – KI – ist ein aktuell viel diskutiertes Thema, welches in vielen Anwendungskontexten eine Rolle spielt. In diesem Beitrag liegt der Fokus auf KI-initiierten und -basierten Innovationen im Dienstleistungskontext. Dazu werden Fragen eruiert, inwieweit sich die Potentiale der KI auf Dienstleistungsinnovationen auswirken, welche Stellhebel zur Gestaltung von KI-gestützten Dienstleistungen existieren, wie KI den Plattformgedanken bereichern kann und wie sich Organisationen dadurch verändern. Mit dem Fokus auf Dienstleistungssysteme werden darüber hinaus die bestehenden Wirkungszusammenhänge diskutiert und die Funktionen von KI als Nukleus, Enabler, Impuls, Grenzobjekt und Innovation zur Dienstleistungsentwicklung eingeführ

Learning to speak “digital” – how industry applies cyber-physical design concepts in new systems implementations - Fritzsche, Albrecht; Oks, Sascha Julian (Information Systems Foundations Workshop: Theorising Digital Innovation, 2016)
Constructs like the internet of things and cyber-physical systems provide a whole new design repertoire for information systems implementations in industry. In our paper, we study three cases in the context of industrial maintenance to explore how companies actually make use of this repertoire in practice and how their usage relates to the potential which is generally associated with the digital transformation of industry. We find that companies use the new repertoire very conservatively and stay closely connected to their previous experience. At the same time, we see that practitioners actively explore directions of digitization which go into rather different directions than those that are currently discussed in public. We interpret this as a first step to the evolution of a general ability to make the new design repertoire usable for specific purposes which can be compared to learning a new languag

Maintenance as a service system in the context of the internet of things - Oks, Sascha Julian; Fritzsche, Albrecht (1st Service Systems Forum, 2015)
The internet of things does not only provide sensorial data to improve the management and control of complex operational networks. It also creates new business opportunities on the basis of value streams that have previously not been accessible. These value streams rely on combinations of human action, technical operation and other resources and can therefore best be described as service systems.Maintenance activities appear to be a particularly promising field of research in this context. Increased sensorial input about the performance of machines and the environmental conditions under which it takes place allows us to identify new weaknesses, predict failures in advance and optimize procedures for parts exchange and repair. This creates a huge savings potential for manufacturing and other industrial operations, which, however, can only be realized if companies rearrange their maintenance procedures and define new roles for the actors in their value creation processes.Our paper presents a comparative study of four different cases in which companies intend to improve their maintenance procedures using the internet of things. This includes car production, the operation of wind energy parks, plant engineering and automotive parts supply. We consider maintenance as a service system that involves different actors with different contributions. For each of the four cases, we describe the specific roles and responsibilities of these actors and their interplay with one another in order to highlight the variety of different possibilities to configure the service system.Our findings indicate that, despite all differences, there is a general need to revise the conception of the competencies and abilities of the people involved in the system in order to create new value streams. Therefore we advocate a user-centered design approach to service systems design in the context of the internet of things and draft a suitable procedure for the cases in questio
Keywords: digitalisation; industry 4.0; cyber-physical systems; internet of things

More than new technical devices: a semiotic look at the digital transformation of industry - Oks, Sascha Julian; Fritzsche, Albrecht (Forum on Philosophy, Engineering & Technology (fPET), 2018)
During the past decade, various programmatic writings have predicted that industry will undergo revolutionary changes in the course of the digital transformation (Kagermann, Wahlster, & Helbig, 2013; Lee, 2006). New engineering approaches in the context of the internet of things, cyber-physical systems and big data are expected to open up radically new paths of technical development (Gölzer & Fritzsche, 2017; Monostori, 2014). They will not only allow the creation of new kinds of technical artefacts, but also alter the process of technical design. In the future, engineering will accordingly be less concerned with the creation of static devices with a determinate function. It will instead revolve much more around the continuous evolution of larger superstructures whose parts have to be updated and adapted in short intervals (Neely, Fell, & Fritzsche, 2018). A clear distinction between design and maintenance tasks in engineering will become increasingly difficult and the work of engineers will rely much more on interactions with other groups of people involved with technology (Fritzsche, 2017). In this paper, we study the effects of the digital transformation on manufacturing processes in industry, where a large number of different programmes have been started to support the introduction of novel technology (Oks, Fritzsche, & Möslein, 2017). We focus in particular on transitions in engineering practice from old to new design and maintenance procedures. We propose that these transitions cannot be appropriately described as an adoption of a new toolset of engineering, but that they rather have to be compared to learning a new language (Franssen & Koller, 2016; Fritzsche & Oks, 2016). As such, they require a deeper semiotic study of the way how meaning is attributed to technology. Observations in different companies allow us to describe the learning process in more detail. All these companies have started projects to implement new technical solutions which involve cyber-physical systems and big data. We look at the way how employees of the companies and their business partners gradually gain “fluency” in the new, digital “language”. We discuss the importance of “active speaking” in contrast to “passive listening”, not only to get a better grasp of the new vocabulary and grammar, but also to motivate the engagement with the new language instead of sticking to the old one. Furthermore, we look at the involvement of new interest groups in engineering, such as maintenance technicians and device users. Their involvement turns the attention to the collective effort necessary to make the transition and the media that allow participation. We present different examples of such media which either support design or maintenance activities. Our findings let us believe that the language-based approach can add an important new perspective to the study of engineering and technology. Current theories of technical artefacts and their design do not seem able to give a full account of the dynamic and fluidity of the digital transformation, especially when it comes to participatory activities in which engineers engage with other groups of people involved with technology
Keywords: Industry 4.0; Digital Transformation

Navigating the Innovation Landscape: Uncovering Dimensions Shaping Technology Transfer Support - Wadlinger, Janik; Oks, Sascha Julian; Möslein, Kathrin (EURAM 2024, 2024)

Open Innovation for the Medical Technology Industry - Daiberl, Christofer; Oks, Sascha Julian (OpenSym: The International Symposium on Open Collaboration, 2014)

Pesquisando a Indústria 4.0: Oportunidades e Desafios - Oks, Sascha Julian; Roth, Angela (EnANPAD 2023, 2023)

Platform-based service composition for manufacturing: A conceptualization - Fuchs, Jonathan; Oks, Sascha Julian; Franke, Jörg (Procedia CIRP, 2019)
With the implementation of cyber-physical production systems, a multitude of isolated industrial services utilizing versatile hardware and software components in heterogeneous and rigid system architectures are an obstacle for the consequent extension of holistic automation within production networks. To address this issue, we conceptualize a platform-based system architecture enabling value-adding service bundles based on and extending proven architectural styles. Our proposal also aims on qualifying communication systems to work transboundary in value-adding networks. The presented architecture is applied to a use case in context of maintenance. Our findings provide an adaptive conceptualization for application-specific service composition and integratio
Keywords: IIoTS platform; service compostion

Potentiale und Risiken künstlicher Intelligenz in der militärischen Ausbildung und Anwendung - Oks, Sascha Julian; Fuchs, Jonathan; Mosig, Tim (Symposium Ausbildung Luftwaffe, 2022)

Potentiale und Risiken künstlicher Intelligenz in der militärischen Ausbildung und Anwendung - Oks, Sascha Julian; Fuchs, Jonathan; Mosig, Tim (Digitale (Aus-) Bildung: Wird Intelligenz tatsächlich „künstlich“?, 2022)
Im Rahmen der voranschreitenden Digitalisierung wird dem technologischen Konzept der künstlichen Intelligenz (KI) eine hohe Relevanz beigemessen. In Verbindung mit weiteren Technologien, wie Big Data-Analysen und Cloud-Anwendungen, bestehen Nutzungsszenarien in unterschiedlichen Domänen. Diese umfassen neben Industrie 4.0, vernetzter Mobilität, dem digitalisierten Gesundheitssystem etc. auch das (Aus-)Bildungswesen und Militär. Welche wichtige Rolle KI damit für die Bundeswehr einnehmen wird, zeigt sich exemplarisch am Future Combat Air System, das ab ca. 2040 den Eurofighter ablösen soll. Für das sich in einem deutschfranzösisch-spanischen Entwicklungsprogramm befindliche Mehrzweckkampfflugzeug stellt KI eine Kernkomponente dar, ohne die die Operation und strategische Nutzung des Plattformsystems unmöglich wäre. Ähnliche Entwicklungen finden in den anderen Teilstreitkräften und Organisationsbereichen der Bundeswehr, insbesondere dem Cyber- und Informationsraum, statt. Der sichere Umgang mit und ein umfassendes Verständnis von KI werden daher für viele Soldaten und Soldatinnen eine essentielle Kernkompetenz. Um dieses Wissen nachhaltig zu vermitteln, findet KI zukünftig auch in kompetenzbasierten Lehr-/Lernformaten vermehrt Anwendung. Der vorliegende Beitrag mit der Methode eines systematischen Literatur-Reviews analysiert diese Entwicklung kritisch aus technologischer, organisationaler und didaktischer Perspektive. Neben einer Kategorisierung von KI-basierten (Aus-)Bildungsverfahren wird dabei besonderes Augenmerk daraufgelegt, inwieweit sich KI-Algorithmen, die in Ausbildung und Material zum Einsatz kommen sollen aber mitunter im Ausland entwickelt wurden, mit den Grundsätzen der inneren Führung, dem Leitbild des Staatsbürgers in Uniform sowie den Prämissen deutscher Sicherheitspolitik in Einklang bringen lassen. Als Ausblick wird das Konzept „künstlicher Ethik“ formuliert, das dem Einsatz von KI einen regulierenden Rahmen setzt.<br

PRODISYS – Engineering Produktionsbasierter Dienstleistungssysteme - Bernard, Michael; Duchon, Markus; Eitner, Felix; Fuchs, Jonathan; Kipouridis, Orthodoxos; Mosig, Tim; Neubert, Colette; Oks, Sascha Julian; Rehman, Kasim; Reidt, Andreas; Stelzner, Jörg; Weiss, Steffen (2021)
Keywords: Service; Industrie 4.0

Produzierende Unternehmen in Deutschland auf dem Weg zu Industrie 4.0 - Erste Erkenntnisse auf Basis einer Delphi-Studie - Seif, Heiko; Puchan, Jörg; Mayer, Dennis; Möslein, Kathrin; Jung, Hans H.; Oks, Sascha Julian (11. Symposium für Vorausschau und Technologieplanung, 2015)
Diese Studie untersucht den aktuellen Fortschritt von produzierenden Unternehmen zu Industrie 4.0. Die Studie zielt darauf ab, produzierende Unternehmen bezüglich Industrie 4.0 zu bewerten, ihren Leistungsstand miteinander zu vergleichen und aus den gewonnenen Erkenntnissen deren Zukunftsfähigkeit sowie Leistungssteigerungsszenarien anhand eines Industrie 4.0 Reifegradmodells aufzuzeigen. Als Grundlage für die Delphi-Studie dient ein selbst entwickeltes Strukturierungsmodell, das die beiden Dimensionen „Herstellungsmerkmale“ und „Industrie 4.0 Merkmale“ in einem Modell vereint und vor Beginn der Studie durch Literaturrecherche und Expertengespräche verifiziert wurde. Für die Bewertung werden aus neun identifizierten Handlungsfeldern die vier zentralen Industrie 4.0-Handlungsfelder „Vernetzung durch horizontale und vertikale Integration“, „Produktion & Logistik“, „Marketing, Vertrieb, Service“ und „Mensch & Organisation“ beleuchtet. Aus der Onlinebefragung von 45 Vertretern produzierender Unternehmen geht hervor, dass der Fortschritt zu Industrie 4.0 sehr stark untereinander und in allen vier Handlungsfeldern variiert. Auf Basis von 49 Bewertungskriterien lässt sich ein Zusammenhang des Fortschritts von Industrie 4.0 mit dem Prozessmanagement sowie dem IT-Anteil der Produkte und der IT-Ausstattung in der Produktion bestätigen. Ferner lässt sich ein Zusammenhang zwischen der Größe eines Unternehmens, gemessen an der Mitarbeiterzahl und an der Umsatzerwirtschaftung und dem Fortschritt zu Industrie 4.0, erkennen. Ein Zusammenhang zwischen dem Produktportfolio eines Unternehmens (kundenindividuelle Produkte vs. standardisierte Produkte) und dem Fortschritt zu Industrie 4.0 kann nicht bestätigt werden. Für die strategische Ausrichtung eines Unternehmens (Differenzierungsstrategie vs. Kosten-führerschaft) kann ebenfalls kein Zusammenhang mit der Reife bezüglich Industrie 4.0 identifiziert werden. Für das dafür angewandte Industrie 4.0-Reifegradmodell wird der Aufbau und die Anwendungssystematik des Process and Enterprise Maturity Model (PEMM) von HAMMER verwendet. Die zugehörigen Inhalte und Handlungsfelder leiten sich aus dem eigens entwickelten Strukturierungsmodell zu Industrie 4.0 sowie aus den Ergebnissen der Studie ab. Erste Ergebnisse der hier referenzierten Studie wurden im Tagungsband zur 28. Jahrestagung des Arbeitskreises Wirtschaftsinformatik der deutschsprachigen Fachhochschulen (AKWI) in Luzern, September 2015, veröffentlicht [PSM15] und für das 10. Symposium für Vorausschau und Technologieplanung erweiter
Keywords: Digitalisierung; Industrie 4.0; Reifegradmodell; Delphi-Studie

Qualifikationsbedarfe im Wandel – Implikationen aus Industrie 4.0 zur Ausarbeitung eines Qualifikationsübersetzungsschlüssels zwischen zivilen und militärischen Fähigkeiten - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin ((Aus)Bildungskongress der Bundeswehr, 2017)
Ebenso wie in zivilen Unternehmen durchläuft die Personal- und Organisationsentwicklung der Bundeswehr (BW) momentan grundlegende Veränderungen. Im Gegensatz zum zivilen Arbeitsmarkt ergibt sich der Handlungsbedarf bei der BW jedoch nicht nur aus technisch-ökonomischen Trends wie Digitalisierung und Industrie 4.0, sondern auch aus geo- und sicherheitspolitischen Lageänderungen aufgrund des aktuellen Zeitgeschehens (Ukraine-Konflikt, zunehmende Einsatzbelastung der BW, etc.). Obendrein verstärkt sich der Konkurrenzdruck auf die BW von zivilen Wettbewerbern auf dem Arbeitsmarkt, der durch gute Beschäftigungsquote und demographischen Wandel ein sinkendes Arbeitskraftangebot nach sich zieht. Steigender Personalbedarf im Rahmen der „Trendwende Personal“ verschärft diese Situation zusätzlich. Die Agenda „Bundeswehr in Führung – Aktiv. Attraktiv. Anders.“ soll die Personaldecke der BW an Führungs- und Fachkräfte quantitativ und qualitativ nachhaltig verbessern. Diese kann nur gelingen, wenn bei der Umsetzung geeignete Analyse- und Steuerungsinstrumente angewendet werden. Basierend auf aktuellen Arbeiten aus der Wirtschaftsinformatik zu Industrie 4.0 stellt der vorliegende Beitrag hierzu das Konzept eines Qualifikationsübersetzungsschlüssels vor, der den Transfer ziviler Qualifikationen und Fähigkeiten insbesondere im Bereich IT-gestützter Tätigkeiten in militärische Anforderungsprofile erleichtert und systematisiert. Der Schlüssel ermöglicht zum einen die bessere Einplanbarkeit von Seiteneinsteigern und Reservisten (bspw. im Fall von § 43 Abs. 3 i. V. m. § 26 Abs. 4 SLV) und zum anderen die Eingliederung von Zeitsoldat*innen in den zivilen Arbeitsmarkt. Die Granularität des Schlüssels ist dabei spezifischer als das ATN-Level gewählt und berücksichtig das genaue Tätigkeitsprofil eines Dienstpostens in Kombination mit der jeweiligen individuellen (beruflichen) Biographie. Der Schlüssel bietet somit Potentiale, die weitere Umsetzung der „Trendwende Personal“ und der „Konzeption der Reserve“ effektiv zu unterstützen sowie die allgemeine Aufwuchsfähigkeit fähigkeitsorientierter zu gestalten.<br
Keywords: Industrie 4.0; Qualifikation; Bundeswehr

Rollen, Views und Schnittstellen – Implikationen zur stakeholderzentrierten Entwicklung Sozio-Cyber-Physischer Systeme - Oks, Sascha Julian; Fritzsche, Albrecht; Möslein, Kathrin (S-CPS: Ressourcen-Cockpit für Sozio-Cyber-Physische Systeme, 2017)
Der Einsatz cyber-physischer Systeme im Industrie 4.0-Kontext verändert die industrielle Wertschöpfung nachhaltig. Die Fertigung „smarter“ Produkte nach kundenindividuellen Wünschen in „Batch Size One“, die zunehmende Hybridität von Produkten und Dienstleistungen sowie die Verfügbarkeit immenser Datenmengen aus der Produktion und dem Produktlebenszyklus, erhöhen die Prozesskomplexität fortlaufend. Dies gilt auch für nachgelagerte, wertschöpfungsunterstützende Services, wie die Instandhaltung. Der vorliegende Beitrag beschreibt die im Rahmen des Förderprojekts „Ressourcen-Cockpit für Sozio-Cyber-Physische Systeme“ (SCPS), das ein Instandhaltungssystem basierend auf einem cyber-physischen System entwickelt, durchgeführten Tätigkeiten zur Ausarbeitung von Rollen, Views und Schnittstellen für dieses System. Dazu werden zunächst cyber-physische Systeme sowie Theorien und Methoden zur stakeholderzentrierten Systementwicklung vorgestellt. Darauf folgend werden das methodische Vorgehen und dessen Ergebnisse in Form eines Rollenmodells und System-Mockups präsentiert. Abschließend werden die generalisierten Erkenntnisse aus dem Projekt beschrieben sowie ein Ausblick für anschließende Forschung gegebe
Keywords: Cyber-physische Systeme; Industrie 4.0; Stakeholder

Service-based integration of modular control components in digital manufacturing platforms - Fuchs, Jonathan; Schneider, Ruwen; Oks, Sascha Julian; Franke, Jörg (2021 IEEE 19th International Conference on Industrial Informatics (INDIN), 2021)
Due to increasing complexity on the shop floor associated with the digital transformation and growing penetration of modern production environments with smart services, the operational phase of automated production facilities is gaining additional importance. The growing range of hybrid service bundles, i.e., the combination of digital services and cyber-physical production systems (CPPS), is expanding the scope of utilization and requires the application of platform-based solutions for service integration. Efficient, scalable IT infrastructures as well as technological flexibility and independence are premises for the successful implementation of these platforms. The availability of ubiquitous communication for seamless networking of all entities also plays a central role. These prerequisites enable the vertical integration of automation components on the shop floor up to the context of strategic business processes based on continuous data and information models. This paper presents an approach for integrating CPPS elements into scalable, highly available service platforms and shows how modern control approaches can be successfully linked with smart service concepts. The exemplary use case for this is a test bench for electric drive
Keywords: Smart Service; Service Bundle; Service Orchestration; Cyber-Physical Microservices; Cyber-Physical Production Systems

Smart City – Die digitale Transformation deutscher Städte und Gemeinden - Oks, Sascha Julian; Howaldt, Tim; Möslein, Kathrin; Korff, Christian; Steinmetz, Ingeborg (2018)

Smart Services - Genennig, Stefan; Hunke, Fabian; Jonas, Julia; Möslein, Kathrin; Oks, Sascha Julian; Satzger, Gerhard; Schüritz, Ronny; Schymanietz, Martin; Seebacher, Stefan (2017)

The digitalisation of industry from a strategic perspective - Oks, Sascha Julian; Fritzsche, Albrecht; Lehmann, Claudia (R&D Management Conference (RADMA), 2016)
Being exposed to technical change with potentially disruptive consequences for their own business operations, managers often hesitate to adopt it. This is currently the case for the digitalisation of industry. We argue in our paper that this is the result of a lack of strategic reflection: in order to engage more actively with innovations of this kind, managers need to put new technical devices in a business context where they can assess them with respect to certain purposes and success criteria. An empirical study on the introduction of a cyber-physical system for industrial maintenance in a variety of different fields of industry provides detailed information about how this is done. Problem-centred interviews are used to collect data on the various ways how decision makers in industry connect innovations in the course of digitalisation to strategic thought. The results highlight important differences between the respective application domains and the stakeholders who are affected by the innovatio
Keywords: digitalisation; industry 4.0; cyber-physical systems

The Future of Engineering: Philosophical Foundations, Ethical Problems and Application Cases - Fritzsche, Albrecht; Oks, Sascha Julian (Springer, 2018)
In a world permeated by digital technology, engineering is involved in every aspect of human life. Engineers address a wider range of design problems than ever before, raising new questions and challenges regarding their work, as boundaries between engineering, management, politics, education and art disappear in the face of comprehensive socio-technical systems. It is therefore necessary to review our understanding of engineering practice, expertise and responsibility. This book advances the idea that the future of engineering will not be driven by a static view of a closed discipline, but rather will result from a continuous dialogue between different stakeholders involved in the design and application of technical artefacts. Based on papers presented at the 2016 conference of the forum for Philosophy, Engineering and Technology (fPET) in Nuremberg, Germany, the book features contributions by philosophers, engineers and managers from academia and industry, who discuss current and upcoming issues in engineering from a wide variety of different perspectives. They cover topics such as problem solving strategies and value-sensitive design, experimentation and simulation, engineering knowledge and education, interdisciplinary collaboration, sustainability, risk and privacy. The different contributions in combination draw a comprehensive picture of efforts worldwide to come to terms with engineering, its foundations in philosophy, the ethical problems it causes, and its effect on the ongoing development of societ

Translations of Technology and the Future of Engineering - Fritzsche, Albrecht; Oks, Sascha Julian (The Future of Engineering: Philosophical Foundations, Ethical Problems and Application Cases, 2018)
Philosophers of technology, engineers, and other experts involved with the same subject matter look at technology in different ways. This paper explores what happens if conflicts and misunderstandings between them cannot be resolved. The exchange between the different expert groups on philosophical questions concerning technology is described as a continuous practice of coping with diversity. This practice can be described as translation, because it connects otherwise unrelated expressions of meaning. It lays the foundation for any further productive treatment of technology in society and future possibilities for the development of engineering. The chapters of this book are used as an illustration of the many different faces and levels of translation in the fiel
Keywords: Empirical turn; Post-normal engineering; Diversity; Translation

Von Schach zu digitalen Wargames – Eine systematische Analyse des Einsatzes spielerischer Elemente in der militärischen Ausbildung - Oks, Sascha Julian; Lehmann, Claudia (Game-based Learning und SeriousGaming für eine starke Demokratie – Chancen und Grenzen, 2024)
Militärisch geführte Auseinandersetzungen verfügen seit jeher über eine multidimensionale Komplexität, die sich aus der Interdependenz verschiedener Faktoren wie geopolitischen Interessen, technischen Systemen, dynamischen Lagebildern und asymmetrischen Konfliktdynamiken ergibt. Durch die voranschreitende Digitalisierung hat sich diese Komplexität noch weiter verstärkt, was unter anderem daran zu erkennen ist, dass die Bundeswehr mit der Aufstellung des Cyber- und Informationsraumes (CIR) als eigenständigem militärischen Organisationsbereich und dessen kürzlicher Etablierung als vierte Teilstreitkraft dieser Entwicklung Rechnung trägt. Komplexität stellt für die fundierte menschliche Entscheidungsfindung jedoch einen Hemmfaktor dar, der insbesondere das Führungspersonal militärischer Einrichtungen und Verbände vor Herausforderungen stellt. Um den Umgang mit Komplexität zu erlernen und diese zielgerichtet in der militärischen Ausbildung regulieren zu können, kommen seit jeher spielerische Elemente zu diesem Zweck zum Einsatz. Das Schachspiel, der Sandkasten als Geländemodell oder computergestützte Simulationen zeigen die weite Bandbreite und facettenreichen Einsatzmöglichkeiten auf. Der vorliegende Beitrag analysiert mit der Methode eines systematischen Literatur-Reviews diese Entwicklung kritisch aus technologischer, organisationaler und didaktischer Perspektive. Dabei wird besonderes Augenmerk daraufgelegt, inwieweit sich bestehende Ausbildungsformate in der Bundeswehr mit Wargames ergänzen lassen. Als Ergebnis wird eine Taxonomie vorgestellt, die eine systematische Übersicht über die Zielsetzungen, Einsatzmöglichkeiten und technischen Komponenten von Wargames bietet und deren kritische Bewertung ermöglicht.<br

Zahlen und Fakten zu Medical Valley Innovation - Oks, Sascha Julian; Daiberl, Christofer (Connecting People, Innovating Health Care - Eine Fallstudie aus dem Medical Valley EMN, 2015)
Keywords: Open Innovation; Innovationsplattform; Medizintechnik